Pengaruh Faktor ESG (Environmental, Social, Governance) terhadap Kinerja Portofolio Investasi Jangka Panjang - Ardhi, Fillah; Adi P, Teguh; Aditya, Farhan; Yovita R Pandin, Maria (Teewan Journal Solutions, 2025)
This research aims to explore the integration of ESG (Environmental, Social, and Governance) factors in the investment decision making process. Using a multimethod approach, this study applies secondary data analysis, ESG assessments and rankings, qualitative analysis of case studies, as well as simulation and portfolio analysis. Secondary data analysis reveals material trends, risks and opportunities related to ESG indicators that may affect long-term investment performance. Internal ESG assessments and ratings or through leading data providers are used to evaluate the ESG performance of companies. Interviews with investment managers, analysts and company representatives provide insight into ESG perceptions, practices and implementation challenges. Qualitative case studies reveal the dynamics and real impacts of ESG integration at the company level. Portfolio analysis and simulations help optimize investment composition by considering ESG factors. The findings of this research provide a comprehensive framework for investors to apply ESG considerations that are aligned with the principles of sustainability and social responsibility, while generating optimal returns in the long term. These results contribute to the development of more holistic and socially and environmentally responsible investment strategies.